NET BENEFITS OF USING ZAHIR ACCOUNTING SOFTWARE IN THE USER'S PERSPECTIVE - Ayu Ningtiyas; Emmy Indrayani (JRAK, 2022)
This research aims at examining and analyzing the effect of system quality, information, and services on user usage and satisfaction. Moreover, the user usage and satisfaction on net benefits provided by Zahir Accounting Software using the Delone and Mclean models. Then, the analysis of this research used SEM-PLS as the analytical tool. Furthermore, The selection of this research sample used purposive sampling on companies who used Zahir Accounting Software in Indonesia as many as 100 respondents. The method of collecting data was done by making an online questionnaire using Google Form. In conclusion, The results showed that the net benefits of using Zahir Accounting Software were influenced by user satisfaction, while user usage did not give any influence on it.